PREDICTING SENTIMENT FROM MOVIE REVIEWS USING LEXICON BASED MODEL - Verma, Binita; Thakur, Ramjeevan Singh; Jaloree, Shailesh (International Journal of Computer Sciences and Engineering, 2025)
Large number of users shares their opinion on social networking sites. So, on the web an enormous quantity of data is generated daily. Usually there is not enough human resource to examine this data. The methods for automatic opinion mining on online data are becoming increasingly. From the past few years, methods have been developed that can successfully analyze the sentiment from digital text. These developments enable research into prediction of sentiment. Sentiment prediction has been used as a tool for movie review prediction. The aim of this work is to explore the use of lexicons to extract the sentiment prediction for a number of movie reviews. In this paper, a comparative analysis of lexicon based models has to predict the sentiments of movie reviews dataset together with evaluation metrics